Effect of sheep's milk composition on strength and syneresis of rennet-induced milk gel during lactation - Rako, Ante, agronom (Array, 2019)
This study investigates the effects of raw sheep’s milk composition on the strength and syneresis of obtained gels throughout the lactation. Casein, fat and total solids content, as well as ionic calcium mass fraction significantly (p<0.05) increased during lactation. As lactation progressed, milk formed firmer gel with higher syneresis ability. Increasing casein to fat ratio in sheep’s milk significantly increased (p<0.05) gel strength and syneresis. On the other hand, gel strength and syneresis were significantly reduced as a result of increased fat content in sheep’s milk. Ionic calcium mass fraction affected gel strength but not syneresis. Neither gel strength nor syneresis were affected by casein and urea content or by somatic cell count in sheep’s milk. Correlation coefficients between milk components and gel strength, as well as syneresis, were significant (p<0.01, p<0.05) but never higher than 0.35.